HUBUNGAN ANTARA KONTROL DIRI DENGAN GAYA HIDUP HEDONISME PADA ANGGOTA YANMA POLDA JATENG - Wahyu Imam Budi Sampurno; An Riwi Widyastuti (IMAGE, 2024)
This research was conducted with the aim of finding out the relationship between self-control and a hedonistic lifestyle. The sample used in this research was all 149 members of the Yanma Polda Jateng. The sampling technique used was saturated sampling. The measuring tool used is a hedonism lifestyle scale based on the aspects stated by Kotler and Armstrong (2010), namely activities, interests and opinions. Hedonism lifestyle scale with a reliability coefficient of 0.968. The self-control scale refers to aspects proposed by Talib (2010), namely the ability to control behavior, the ability to control cognitive abilities and the ability to control decisions. Self-control scale with a reliability coefficient of 0.980. To analyze the relationship between the two variables in this study, the data analysis used was the Spearman's Rho method. The results of the research show that there is a significant negative relationship between self-control and the hedonistic lifestyle of members of the Yanma Polda Jaten with a value of rs = -0.673 with a p value = 0.000 (p < 1%) meaning that there is a significant negative relationship between self-control with a hedonic lifestyle among members of the Yanma Polda Central Java with an effective contribution from the self-control variable to a hedonistic lifestyle of 70.2% while the rest is influenced by other variables. Keywords: hedonistic lifestyle, self-control